2020
DOI: 10.1186/s40658-020-00334-7
|View full text |Cite
|
Sign up to set email alerts
|

High-quality brain perfusion SPECT images may be achieved with a high-speed recording using 360° CZT camera

Abstract: Objective The aim of this study was to compare brain perfusion SPECT obtained from a 360° CZT and a conventional Anger camera. Methods The 360° CZT camera utilizing a brain configuration, with 12 detectors surrounding the head, was compared to a 2-head Anger camera for count sensitivity and image quality on 30-min SPECT recordings from a brain phantom and from 99mTc-HMPAO brain perfusion in 2 groups of 21 patients investigated with the CZT and Anger cameras, respectively. Image reconstruction was adjusted ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 38 publications
(31 reference statements)
0
24
0
1
Order By: Relevance
“…Clinical applications of CZT-based SPECT initially began with dedicated cardiac SPECT systems, which were reported to acquire images in a shorter time than conventional systems 3 , 4 . Subsequently, companies began marketing whole-body SPECT/CT using CZT detectors, and the possibility of a short-time scan (STS) has been reported in cardiac 5 , brain 6 , 7 , and whole-body bone scan 8 . However, it is as yet unknown whether or not short-time acquisition is acceptable for clinical applications related to SPECT/CT bone imaging using CZT detectors.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical applications of CZT-based SPECT initially began with dedicated cardiac SPECT systems, which were reported to acquire images in a shorter time than conventional systems 3 , 4 . Subsequently, companies began marketing whole-body SPECT/CT using CZT detectors, and the possibility of a short-time scan (STS) has been reported in cardiac 5 , brain 6 , 7 , and whole-body bone scan 8 . However, it is as yet unknown whether or not short-time acquisition is acceptable for clinical applications related to SPECT/CT bone imaging using CZT detectors.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to PET, SPECT images suffer from limited spatial resolution. This is partially inherent in the physics of the technique, however there have been significant improvements in SPECT spatial resolution with the introduction of high sensitivity solid state detectors such as Cadmium zinc telluride (CTZ) and Cesium Iodide (CsI) as compared to a conventional Anger camera ( 8 ).…”
Section: Spect Vs Petmentioning
confidence: 99%
“…A 5 cm translation of the VOI was subsequently applied to measure mean background activity ("Mean BKG" in counts per second) and corresponding standard deviation ("SD BKG"). Contrast-to-noise ratio was nally computed with the following equation [19]:…”
Section: Image Reconstructions and Analysismentioning
confidence: 99%
“…The whole-body Veriton® camera (Spectrum Dynamics Medical, Caesarea, Israel) combines CZT detectors with an original 360° ring-con guration geometry that allows the detectors to be positioned very close to the patient, a con guration that is likely to maximize both count sensitivity and image quality [17][18][19]. With this camera, it has already been demonstrated that a whole-body 3-dimensional SPECT recording may be obtained in no more than 20 minutes for bone 99m Tc-scintigraphy [17], as well as for lutetium-177 therapeutic imaging [18].…”
Section: Introductionmentioning
confidence: 99%